Re-distribution of income in favor of the poor - theoretical entrance of stagnation treatment - العنبكي, عبد الحسين (Journal of Economics and Administrative Sciences, 2014)
Research deals the crises of the global recession of the facets of different and calls for the need to think out of the ordinary theory and find the arguments of the theory to accommodate the evolution of life, globalization and technological change and the standard of living of individuals and the size of the disparity in income distribution is not on the national level, but also at the global level as well, without paying attention to the potential resistance for thought the usual classical, Where the greater the returns of factors of production, the consumption will increase, and that the marginal propensity to consume may rise and the rise at rates greater with slices of low-income (the mouths of the poor) with a view to satisfy the needs of non-saturated, and increasing investment demand when increasing marginal efficiency of capital in excess of the interest rate, Thus, the national income liege a positive function relation with (investment) and greater return on investment encourage organizers to greater investment ROI Vtkon relationship positive correlation between the size of the investment and earnings expectations for, and then will be affected the level of development at rates profits long as it is function in the investment. Government interventions (demand management) lengthened the life crises, but at the same time prevented it that magnified to the extent of out of control, it is permission from the corner boosted Immunologists economy depending on government intervention and made at the same time autoimmune economies back down as it has become in the custody of government Macro policies , which reduced the ability of markets to adapt and become a market mechanism is ineffective Other (the sticky) in their ability to work to restore balance and stability, In order to continue investment demand would have to proceed with consumer demand in order to find the balance and the liquidation of the market and otherwise occurring crises, stagnation, and so is moving consumer demand sufficiently to push investments and achieving profits must satiating the mouths of the poor continually, and this confirms that the solution to the crisis of stagnation, and in order not to shrinks investments capitalists and their profits shrinks by extension they should think hard about manner for the distribution of returns of production factors in a fair and equitable manner.What is new is that what he deserves every factors of the production of the returns is no longer gets it in accordance with the mechanisms of compete, so it is no longer the four factors of production, and we have to change theoretical framework to become the five factors of production, to become a technology one of the factors of production fundamental and not a follower or followed by appear its effect incarnated in the capital sometimes or non-incarnated but just (residuals) such as technical knowledge, experience and good organization and others, if the state is the administration and the private sector is the economy, the mix optimizing between the administration and the economy ensures us the prevalence of the social market economy in order to achieve sustainable development, and this limits the emergence of large and rotating stagnation  crises.